PENERAPAN TEKNIK AKROSTIK MELALUI AKTIVITAS TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA KELAS V SDN DODA - Nelvin, Nelvin (BAHASANTODEA, 2015)
Abstract This research aimed to improve the ability to write poetry with guided activities of the fifth grader of SDN Doda. This research was a classroom action research. It used aspect of treatment and main observation, namely an increase in the ability to write treatments and that the main observation of the writer used the acrostic method. The research design used Kemmis research design and Mc. Taggart. This research consisted of two cycles, each cycle held two meetings in the class and each cycle consisted of four stages: planning, implementation, observation and reflection.Â  The indicators of individual criteria of succes was 70% and classical criteria of succes 80%. The writing assessment component are the object, diction, rhyme, mandate, and a figure of speech. By product, increasing the ability to write writing poetry ability could be seen based on those data analysis of increasing value in writing poetry of the students. The results of the average value of individual student mastery of writing poetry in the first cycle was 59% and classical achievements in the first cycle was 65%. In cycle 2, there was significant increasing, the average value of individual achievement of writing poetry was 85.25% and classical achievement was 90%. Therefore, it concluded that learning by using acrostic method could develop the ability in writing poetry of Class V students at SDN Doda. Keywords: Writing Poetry, Guided Activity